Studi Potensi Teknologi Hologram Untuk Meningkatkan Wawasan Kebangsaan Gen Alpha - Yasmin Yasmin; Yusrotul Latifa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The era of society 5.0 is part of the history of technological development. Technology is present in every human activity. The wise use of technology can create extraordinary cognitive abilities. In an effort to realize the golden Indonesia 2045 and feel the demographic bonus 2030, all parties are expected to be able to contribute, especially teachers and parents. In this study, we focus on efforts to increase Indonesian national insight by the Alpha generation through learning using holograms to realize the Golden Indonesia 2045. The Alpha generation, which is believed to live side by side with technology, has several concerns such as decreased cognitive, focus and social abilities. This study uses a literature study to determine the potential of holograms in increasing national insight. The discussion that we present begins with the parenting pattern of the Alpha generation and the urgency of national insight to foster a sense of love for the homeland and strengthen Indonesian national insight in reducing the impact of the flow of Globalization.